ANALISIS PENGARUH KEDISIPLINAN KERJA GURU TERHADAP PRESTASI BELAJAR SISWA PADA SMA NEGERI 1 BUMIAYU KABUPATEN BREBES - Siti Bariroh (Institut Agama Islam Negeri Purwokerto, 2017)
Discipline is one of the factors of success in achieving learning goals. Discipline teacher will bring a positive impact on the development of students, it requires dedication and a high responsibility. A teacher required to cultivate the mindset, have extensive knowledge, must also have competencies that qualified, good pedagogy, methodology, or disciplines to be taught. The teaching profession is a noble profession, although sometimes underestimated, but it is crucial in preparing the next generation, which will continue nation's leadership in the future. Teachers are also required to be able to provide examples of good models, in order to produce generations that can be better in the future. xThe benchmark of whether good nor bad of one community is the education itself. While the main character in the world of education is the teacher, because the teacher are able to single handedly carve a student's future whether it's good nor bad.The people's expectation on the products of the education system can be seen on the student's both academic and non-academic achievements.This research is using a quantitative descriptive method, whereas the type of approach used in this study is a partial correlation by analyzing the relationship (influence) between the variables of work discipline in the teacher with student achievement.Data collection technique is to spread the Likert scale questionnaire form which contains a number of questions about the indicators of work discipline and student achievement. The data obtained was then added to the partial correlation formula per variable, then connected, whether there is a significant relationship between teacher's work discipline with student achievement in SMA Negeri 1 Bumiayu, Brebes Regency, while the author used determinant coefficient to analyze the relationship between teacher's work discipline and student achievement.The results of the study is showing that teacher's work discipline will affect student achievement, because there is a relationship of 0.786 or 78.6% that were classified as very strong based on the level of its relationship.